A DESCRIPTIVE STUDY ON FIGURATIVE LANGUAGE IN TIMORESE SONGS - Riwu, Ririn; Dethan, Erniani O; Tlonaen, Zuvyati (Journal of Language, Education, Literature, and Culture, 2023)
Songs are written in artistic language. The artistic language is called figurative language in literature. This study is a descriptive study of figurative language in traditional Timorese songs. Timorese songs have figurative meanings hidden in the lyrics. Finding out figurative language's types and meanings is exciting and challenging. Therefore, the research objectives are to identify the types of figurative language and their meanings. This study was a documentary study using the qualitative method. The data was collected by reviewing 11 Timorese songs. The research procedures were downloading the songs (videos) from YouTube, transcribing and translating the data, identifying the figurative language, classifying them into types, analyzing and interpreting the meanings, and concluding. Data analysis used Miles and Huberman's data analysis; data reduction, data display, and data conclusion or verification. The research found seven types of figurative language; 1) simile (four sentences), 2) metaphor (three sentences), 3) allegory (four sentences), 4) personification (four sentences), 5) antonomasia (one sentence), and 6) epithet (three sentences). Figurative language in Timorese songs is a description the songwriter uses to explain meaning through unusual comparisons to attract attention and make something more straightforward. Future research on figurative language in traditional songs can be done to find more types and meanings.